Bioactive Properties of the Stone Fish Synanceia horrida Thomas 1984 Spine Venom - Prithiviraj, N (International Journal of Pharmaceutical & Biological Archive, 2012)
Bioactive Properties of the Stone Fish Synanceia horrida Thomas 1984 Spine Venom